Cognitive decline in older adults: What can we learn from optical coherence tomography (OCT)‐based retinal vascular imaging?. Issue 9 (19th May 2021) - Abraham, Alison G.; Guo, Xinxing; Arsiwala, Lubaina T.; Dong, Yanan; Sharrett, A. Richey; Huang, David; You, Qisheng; Liu, Liang; Lujan, Brandon J.; Tomlinson, Alexander; Mosley, Thomas; Coresh, Josef; et al.
Abstract: Introduction: Accumulated vascular damage contributes to the onset and progression of vascular dementia and possibly to Alzheimer's disease. Here we evaluate the feasibility and utility of using retinal imaging of microvascular markers to identify older adults at risk of cognitive disease. Methods: The "Eye Determinants of Cognition" (EyeDOC) study recruited a biracial, population‐based sample of participants from two sites: Jackson, MS, and Washington Co, MD. Optical coherence tomographic angiography (OCTA) was used to capture vessel density (VD) from a 6 × 6 mm scan of the macula in several vascular layers from 2017 to 2019. The foveal avascular zone (FAZ) area was also estimated. Image quality was assessed by trained graders at a reading center. A neurocognitive battery of 10 tests was administered at three time points from 2011 to 2019 and incident mild cognitive impairement (MCI)/dementia cases were ascertained. Linear mixed‐effects models were used to evaluate associations of retinal vascular markers with cognitive factor score change over time. Results: Nine‐hundred and seventy‐six older adults (mean age of 78.7 (± 4.4) years, 44% black) were imaged. Gradable images were obtained in 55% (535/976), with low signal strength (66%) and motion artifact (22%) being the largest contributors to poor quality. Among the 297 participants with both high‐quality images and no clinically significant retinal pathology, the average decline in global cognitive function factor score was −0.03 standard deviations per year. In adjusted analyses, no associations of VD or FAZ with longitudinal changes in either global cognitive function or with incident MCI/dementia were found. Conclusions: In this large biracial community sample of older adults representative of the target population for retinal screening of cognitive risk, we found that obtaining high‐quality OCTA scans was infeasible in a nearly half of older adults. Among the select sample of healthier older adults with scans, OCTA markers were not predictive of cognitive impairment.